Análisis de la demografía empresarial del Perú según actividad económica periodo 2020 – 2021 - Rengifo Tapullima, Leysir (2024)
The 2020 crisis affected the country in all its structures, and the business sector was no exception and had to behave disruptively to continue operating in the market. This doctoral thesis is carried out with the objective of analyzing the business demography of Peru according to economic activity in the period 2020 - 2021. Guided by this objective, research of a Quantitative nature is carried out, with a Descriptive level of explanation and with a NonExperimental design. The results of the investigation guide the conclusions, the first of which is that the stock of companies in Peru is predominantly concentrated in the Retail Trade economic activity, since 31.09% of them exercise it, reaching the figure of 926,946 units. Neighborhood wineries are located in this segment as the most notorious enterprises. On the other hand, the analysis of the stock of companies according to their legal organization shows that the Natural Person category contains the largest number of companies that add up to 1,786,274 units, equal to 59.92% of the total. On the other hand, the demographic distribution of the business stock shows that Lima is the department that hosts the largest number of companies, reaching 1,004,445 units, equivalent to 33.69% of the total. Of the stock of existing companies in Peru at the end of the 2020-2021 period, 1,693,860 of them are led by women, equal to 56.82%.